Women and the shaping of British Methodism : persistent preachers, 1807-1907 - Lloyd, Jennifer M. (Gender in history., 2009)
A response to the prominent Methodist historian David Hempton's call to analyse women's experience within Methodism, this book is the first to deal with British Methodist women preachers over the entire 19th century.